The Reduction of Criminal Justice Policy in Indonesia: Justice versus Virality - Muhammad, Rustamaji; Shalih Mangara Sitompul; Tojiboyev Sarvar Zafarovich; Rahimah Embong (Lembaga Contrarius Indonesia, 2025)
The phenomenon of virality on social media has had a significant impact on the criminal justice system in Indonesia. Digital public pressure can influence the speed and direction of law enforcement, even shifting fundamental principles such as the principles of legality, equality before the law, and due process of law. This study aims to analyze how virality influences criminal justice policy, identify forms of reduction and erosion of criminal law policy, and formulate a balanced approach between legal justice and digital public pressure. This study uses a normative juridical method with three approaches: a legislative approach, a conceptual approach, and a comparative approach. The results show, first, that virality has shifted the orientation of law enforcement in Indonesia, with viral cases such as those involving Ferdy Sambo and Mario Dandy being processed more quickly due to public pressure, rather than legal urgency. Second, this condition indicates a severe reduction in the principles of legality, equality, and due process, exacerbated by ad hoc legislation and reactive executive intervention. Third, while digital publics can promote accountability, Indonesia needs institutional strategies to balance these pressures without compromising legal integrity. Recommendations include reforming legal education based on digital literacy, establishing digital response units within law enforcement agencies, and strengthening media regulations to prevent trial by media. Indonesia needs to restructure its criminal justice policy so that it remains based on constitutional values and the principles of the rule of law, rather than being driven by popularity in the digital space.